Factors Associated with Impaired Humoral Immune Response to mRNA Vaccines in Patients with Inflammatory Bowel Disease: A Matched-Cohort Analysis from the RisCoin Study - Katarina Csollarova; Leandra Koletzko; Thu Giang Le Thi; Paul R. Wratil; Ana Zhelyazkova; Simone Breiteneicher; Marcel Stern; Gaia Lupoli; Tobias Schwerd; Alexander Choukér; Veit Hornung; Oliver T. Keppler; et al. (Vaccines)
Background/Objectives: The SARS-CoV-2 pandemic challenged patients with inflammatory bowel disease (IBD) under immunosuppressive therapies. We used data from the RisCoin cohort to investigate factors associated with a poor immune response to mRNA vaccination in these patients. Methods: From 4115 RisCoin participants, we matched 110 IBD patients by age and time interval since the second mRNA vaccination with 306 healthcare workers (HCW) without comorbidities (HCW-healthy) and 292 with medical conditions (HCW-plus); all were SARS-CoV-2 infection naïve. Basic questionnaires collected data on medication, COVID-19 vaccinations and side-effects, dietary patterns, lifestyle factors, and self-perceived stress. Main outcomes included anti-spike immunoglobulin levels and antibody-mediated live-virus neutralization immunity (NT) to the Omicron BA.1 variant (threshold NT ≥ 10 defined as IC50 values ≥1:10 serum dilution) after the second (baseline) and third vaccinations. Results: At baseline, IBD patients treated with anti-TNF but not those under vedolizumab or ustekinumab therapy had lower anti-spike levels compared to HCW-healthy and HCW-plus (166 versus 1384 and 1258 BAU/mL, respectively; p < 0.0001). Anti-TNF compared to vedolizumab/ustekinumab-treated patients reached NT titers above threshold in 17% versus 64%, respectively, and HCW-subgroups in 73% and 79% (all p < 0.0001). Current smokers showed a four to five times increased risk for non-neutralizing immunity compared to non-smokers. After the third vaccination, NT titers did not reach threshold in 15% anti-TNF compared to 5% vedolizumab/ustekinumab-treated patients and none of HCW (p < 0.01). Patients with IBD reported fewer clinical symptoms after vaccination. Perceived stress was not increased. Conclusions: Our findings support individualized schedules for mRNA-based vaccines in IBD patients with different immunosuppressive therapies and enforcement of non-smoking.